'I gave him Leave to Live': Emily Dickinson's Non-service and Ralph Waldo Emerson. Issue 2 (2nd July 2020) - Kang, Yanbin
Abstract : Considering assistance 'the finest of Joys' (Fr1729), Dickinson singularly espouses withdrawing or withholding giving, regarding at times 'leaving alone' as an essential aspect of perfect assistance. This essay offers a reading of several of Dickinson's poems that relate to the ethics of withholding: including 'To offer brave assistance' (Fr492), 'We grow accustomed to the Dark -' (Fr428), 'I rose - because He sank -' (Fr454), and 'It came his turn to beg -' (Fr1519), arguing that Dickinson's idiosyncratic non-service stems from a creative conversation with the work of Ralph Waldo Emerson.